Pembentukan Karakter Religius Di Madrasah Ibtidaiyah Berbasis Pesantren - Awaliyani Mahmudiyah; Mulyadi Mulyadi (ZAHRA: Research and Tought Elementary School of Islam Journal, 2021)
Madrasah Ibtidaiyah Miftahul Ulum Kesamben Wetan. This study uses a qualitative research method with a case study approach. Data collection techniques using observation, interviews, and documentation. The data analysis technique used the analysis of Miles and Huberman. Test the validity of the data by triangulation and reference adequacy. The results of the research show that the process of building religious character in Islamic elementary schools based on the Miftahul Ulum Kesamben Wetan Islamic Boarding School through dhuha prayer, tahfidzul qur'an, congregational prayer, courtesy, through religious activities such as Eid al-fitr, Eid al adha, sharing zakat, sharing takji, and break fast together. Read the yasin letter every Friday, share on Friday legi, read juz amma ', memorize daily prayers, and do active pesantren activities. The obstacle is synchronizing the vision and mission of the school with what parents expect, there are still children who arrive late, teachers are expected to be more careful in guiding children and providing good examples, children's abilities during the learning process, and children do not want to follow orders from teacher.